Estimating the Volume of Surface Runoff Using a Method (SCS-CN) For the Shahlagha Basin Using Modern Techniques - Aso Swar Namiq (Zanco Journal of Human Sciences, 2025)
The research aims to estimate the amount of surface runoff in the Shahlagha Basin within Erbil Governorate, which is a seasonal basin with an area of (612) km2, based on rain data and morphometric characteristics of the basin, using estimation equations designed by the US Soil Conservation Service (SCS-CN) to achieve this goal. The value of the numerical coefficient (CN) in the basin was calculated between 71-94, which reflects the diversity of Soil characteristics and land use in the area. Factor (S) values ​​were calculated, which ranged between (5.18-103.75). It was found that the (la) value was less than the median value of 50.8 mm, while the value of (Q) for the research area was During the period from (2014-2023) The maximum depth of flow is (45.085) mm after (50.4) mm of rain fell on 4/12/2023. While the lowest depth of flow was recorded at (12.205) mm after (21.15) mm of rain fell on 12/21/2023.The highest value is for the volume of surface drainage (QV) recorded on 4/2023 and amounted to 52.80618 m3, due to a rainstorm of 50.4 mm. While the lowest value was recorded on 12/21/2023 and was 7.469594 m3 due to 21.15 mm of rainfall. These results form a database of surface drainage in the study area that can be used in investment and sustainable management of the basin.